Co / CoS2 / surface porous Si composite photoelectrocatalytic material and preparation method and application thereof

By etching the surface of Si photoelectrocatalytic material to form a porous structure and modifying Co/CoS2 composite powder, the problems of high reflectivity, poor stability and low hydrogen evolution reaction rate of Si photoelectrocatalytic materials are solved, and more efficient photoelectrocatalytic performance is achieved.

CN119121307BActive Publication Date: 2025-03-25HUNAN PETROCHEMICAL VOCATIONAL TECH COLLEGE +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411280528.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-03-25
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

The existing Si photoelectrocatalytic materials have problems such as high reflectivity, poor stability and low hydrogen evolution reaction rate.

Method used

By etching the plane Si into a surface porous Si substrate and modifying the Co/CoS2 composite powder on its surface, the Co/CoS2/surface porous Si composite photoelectrocatalytic material is formed.

Benefits of technology

The reflectivity of the material is reduced, the stability and the rate of hydrogen evolution reaction are improved, and the photoelectrocatalytic performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121307B_ABST
    Figure CN119121307B_ABST
Patent Text Reader

Abstract

The present invention discloses a Co / CoS2 / surface porous Si composite photoelectrocatalytic material and its preparation method and application, belonging to the field of photoelectrocatalytic materials. The preparation method provided by the present invention comprises the following steps: preparing a surface porous Si substrate; uniformly depositing a layer of metal Co on the surface of the surface porous Si substrate to form a Co‑Si composite material; adding the Co‑Si composite material to a sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co‑Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material. The present invention modifies the surface porous Si substrate by Co / CoS2 composite powder, reduces the reflectivity of the material, and improves the stability and the rate of hydrogen evolution reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoelectric catalytic materials, and in particular relates to a Co / CoS2 / surface porous Si composite photoelectric catalytic material and a preparation method and application thereof. Background Art

[0002] Photoelectrocatalytic technology uses solar energy to generate renewable energy. In the process of photoelectrocatalytic reaction, the performance of the catalyst directly affects the efficiency of the reaction. Photoelectrocatalysts mainly include oxynitrides, metal nitrides, metal phosphides, metal vanadates, metal halides, polymers, metal sulfides, metal oxides, Si materials and their corresponding complexes.

[0003] In the prior art, it is a common practice to use single crystal Si materials as photoelectrocatalytic materials. Single crystal Si materials have low material costs, suitable bandgap width, suitable conduction band and valence band positions, so single crystal Si materials show excellent photoelectrochemical water decomposition capabilities. However, from the current research status, there are still many problems with silicon as a photoelectrode. First, silicon has a high light reflectivity, and the part of the incident light that will be reflected is greater than 30%, which restricts the improvement of silicon catalytic efficiency; second, silicon has poor stability in humid air and water; third, the hydrogen evolution reaction on the silicon surface is a slow kinetic process. How to solve the above problems is a technical problem that needs to be solved urgently in this industry. Summary of the invention

[0004] In view of the above-mentioned defects of the prior art, the present invention provides a Co / CoS2 / surface porous Si composite photoelectrocatalytic material and a preparation method and application thereof. The material is prepared by etching planar silicon to form a surface porous Si substrate, and then modifying the surface of the surface porous Si substrate with Co / CoS2 composite powder. The surface porous Si substrate is modified by silicon surface modification and Co / CoS2 composite powder, thereby reducing the reflectivity of the material, improving the stability and the rate of hydrogen evolution reaction, and effectively solving at least one of the technical problems mentioned in the background technology.

[0005] To solve the above problems, the technical solution of the present invention is:

[0006] A method for preparing a Co / CoS2 / surface porous Si composite photoelectrocatalytic material comprises the following steps:

[0007] Step 1, preparing a surface porous Si substrate by using a metal-assisted catalytic etching method;

[0008] Step 2, using chemical cobalt plating to uniformly deposit a layer of metal Co on the surface of the porous Si substrate to form a Co-Si composite material;

[0009] Step 3, adding the Co-Si composite material to the sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co-Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material.

[0010] As an improvement, step 1 specifically includes the following steps:

[0011] Cut the Si wafer into pieces with an area of ​​1-2 cm 2 The small pieces were then ultrasonically rinsed with acetone for 15 min, ethanol for 10 min, and ultrapure water for 5 min.

[0012] Prepare a mixture of concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1, put the rinsed Si wafer into the mixture, soak it at room temperature for 25 minutes, and then soak it in 5% hydrofluoric acid solution for 2 minutes;

[0013] A solution of 4.65 mol / L HF, 0.01 mol / L AgNO3 and 0.05 mol / L H2O2 was placed in a plastic cup, which was placed in a water bath at a constant temperature of 60°C. The Si wafer was then placed in the mixed solution in the plastic cup for etching.

[0014] The etched Si wafer was soaked in concentrated HNO3 for 1 hour to remove the silver particles on the surface and in the pores. After taking it out, the Si wafer was placed in a drying oven and dried at 70°C for 2 hours to obtain a surface porous Si substrate and weigh it accurately.

[0015] As an improvement, the etching time is 40-50 minutes.

[0016] As an improvement, the plating solution used for chemical cobalt plating is weakly alkaline and includes cobalt salt, hypophosphite and complexing agent, wherein the cobalt salt is selected from at least one of cobalt chloride and cobalt sulfate, the concentration of the plating solution is selected to be 0.01-0.04 mol / L, the hypophosphite is used as a reducing agent, the concentration is selected to be 0.1-0.25 mol / L, and the complexing agent is selected from one of sodium citrate and tetrahydroxypropylethylenediamine THPED, and the concentration is selected to be 0.03-0.09 mol / L; the specific process of chemical cobalt plating includes the following steps:

[0017] The surface porous Si substrate is immersed in a 5-10% HF solution for 2 minutes to remove the surface oxide film, and then rinsed with pure water after being taken out; the rinsed surface porous Si substrate is activated with a PdCl2 solution, and then repeatedly rinsed with pure water after activation; the back of the surface porous Si substrate is adhered with a high temperature resistant and corrosion resistant tape to prevent the deposition of a coating on the back of the surface porous Si substrate, and the surface porous Si substrate is immersed in the plating solution for 5-15 seconds to obtain the required Co plating amount, and then repeatedly rinsed with deionized water after being taken out, and a Co-Si composite material is obtained by drying.

[0018] As an improvement, step 3 specifically includes the following steps:

[0019] The Co-Si composite material was activated and pretreated with dilute strong acid and anhydrous ethanol, and the activated Co-Si composite material was vacuum dried at 60°C for 3h;

[0020] Weigh the mass m of the dried Co-Si composite material, and calculate the mass n of the cobalt source in the Co-Si composite material;

[0021] Calculate the mass a of sulfur source required to completely react with the mass n of cobalt source;

[0022] Take a sulfur source with a mass less than a and add it to a mixed solution of 40 mL of deionized water and 40 mL of anhydrous ethanol until the sulfur source is completely dissolved to obtain a colorless transparent solution;

[0023] The dried Co-Si composite material was transferred together with the colorless transparent solution into a 200 mL high-pressure reactor, subjected to solvent thermal reaction at 160-170°C for 6-8 hours, cooled to room temperature, the sample was taken out, and repeatedly washed with deionized water, and then placed in a forced air drying oven at 60°C for 6 hours to obtain a Co / CoS2 / surface porous Si composite material.

[0024] As an improvement, the dilute strong acid is dilute hydrochloric acid, and the sulfur source is sulfur-containing organic matter.

[0025] As an improvement, in the Co / CoS2 / surface porous Si composite material, the content of Co is 3%-5% of the content of CoS2.

[0026] A Co / CoS2 / surface porous Si composite photoelectrocatalytic material is prepared by the above-mentioned preparation method.

[0027] An application of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material as described above is used to prepare a photoelectrocatalytic electrode.

[0028] The beneficial effects of the present invention are:

[0029] A nano Co / CoS2 composite material with high-valent cobalt is synthesized and grown on the surface of a surface porous Si substrate by an in-situ sulfidation method. The nano Co / CoS2 grows on the surface of a surface porous Si substrate with a three-dimensional structure. The two are in close contact, which is beneficial to the transfer and utilization of charges. The composite material has a higher active specific surface area, which is beneficial to providing more catalytic active centers for contact with the electrolyte, and can be well applied to the electrolysis of water for catalytic hydrogen evolution. The invention also has the characteristics of simple process, mild conditions and high stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1Represents the XRD pattern of Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample;

[0031] Figure 2 The full XPS spectrum of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample;

[0032] Figure 3 Represents the SEM image of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample at 200 μm;

[0033] Figure 4 A comparison chart of the UV-visible diffuse reflectance spectra of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material, the planar Si material, the surface porous Si material and the Co / CoS2 / planar Si composite material;

[0034] Figure 5 The photo-hydrogen conversion efficiency diagram of Co / CoS2 / surface porous Si composite photoelectrocatalytic material and Co / CoS2 / planar Si composite material at different etching times;

[0035] Figure 6 A comparison of the photo-to-hydrogen conversion efficiency of Co / CoS2 / surface porous Si composite photoelectrocatalytic materials when the loading amount of Co / CoS2 is 2.1, 3.0 and 3.7 mg respectively;

[0036] Figure 7 A comparison chart showing the light-to-hydrogen conversion efficiency of Co / CoS2 / surface porous Si composite photoelectrocatalytic materials, Co / CoS2 / planar Si composite materials, Co / CoS2 / GCE composite materials, surface porous Si materials and planar Si materials;

[0037] Figure 8 A comparison chart showing the photo-to-hydrogen conversion efficiency of Co / CoS2 / surface porous Si composite photoelectrocatalytic materials under strong light and weak light conditions;

[0038] Fig. 9 A stability curve diagram showing the Co / CoS2 / surface porous Si composite photoelectrocatalytic material. DETAILED DESCRIPTION

[0039] In the description of the present invention, it is necessary to understand that the terms indicating orientation or positional relationship are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the referred elements must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0040] The embodiments of the present invention are further described below in conjunction with the accompanying drawings.

[0041] Example 1

[0042] This embodiment provides a method for preparing a Co / CoS2 / surface porous Si composite photoelectrocatalytic material, comprising the following steps:

[0043] Step 1: Prepare a surface porous Si substrate using a metal-assisted catalytic etching method.

[0044] Step 1 specifically includes the following steps:

[0045] The Si wafer was cut into pieces with an area of ​​2 cm 2 The small pieces were then ultrasonically rinsed with acetone for 15 min, ethanol for 10 min, and ultrapure water for 5 min.

[0046] Prepare a mixture of concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1, put the rinsed Si wafer into the mixture, soak it at room temperature for 25 minutes, and then soak it in 5% hydrofluoric acid solution for 2 minutes;

[0047] A solution of 4.65 mol / L HF, 0.01 mol / L AgNO3 and 0.05 mol / L H2O2 was placed in a plastic cup, which was placed in a water bath at a constant temperature of 60°C. The Si wafer was then placed in the mixed solution in the plastic cup for etching.

[0048] The etched Si wafer was soaked in concentrated HNO3 for 1 hour to remove the silver particles on the surface and in the pores. After taking it out, the Si wafer was placed in a drying oven and dried at 70°C for 2 hours to obtain a surface porous Si substrate and weigh it accurately.

[0049] In order to ensure that dense and fine pores are completely formed on the surface of the Si wafer and to prevent the fine pores from being destroyed due to excessive etching, the etching time is selected to be 45 minutes.

[0050] Step 2: using chemical cobalt plating to uniformly deposit a layer of metal Co on the surface of the porous Si substrate to form a Co-Si composite material.

[0051] The plating solution used for chemical cobalt plating is based on cobalt salt and hypophosphite, and is prepared by adding suitable complexing agents and other additives such as stabilizers, accelerators, surfactants, etc. The solution is weakly alkaline. In the plating solution, the cobalt salt is selected from at least one of cobalt chloride and cobalt sulfate, and the concentration of the plating solution is selected to be 0.03 mol / L. The hypophosphite is used as a reducing agent, and the concentration is selected to be 0.2 mol / L. The complexing agent is selected as sodium citrate, and the concentration is selected to be 0.05 mol / L. The specific process of chemical cobalt plating includes the following steps:

[0052] The surface porous Si substrate is immersed in a 6% HF solution for 2 minutes to remove the surface oxide film, and is rinsed with pure water after being taken out; the rinsed surface porous Si substrate is activated with a PdCl2 solution, and is repeatedly rinsed with pure water after activation; the back of the surface porous Si substrate is adhered with a high temperature resistant and corrosion resistant tape to prevent the deposition of a coating on the back of the surface porous Si substrate, the surface porous Si substrate is immersed in the plating solution for 12 seconds to obtain the required Co plating amount, and is repeatedly rinsed with deionized water after being taken out, and a Co-Si composite material is obtained by drying.

[0053] Step 3, adding the Co-Si composite material to the sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co-Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material.

[0054] Step 3 specifically includes the following steps:

[0055] The Co-Si composite material was activated and pretreated with dilute strong acid and anhydrous ethanol, and the activated Co-Si composite material was vacuum dried at 60°C for 3h;

[0056] Weigh the mass m of the dried Co-Si composite material, and calculate the mass n of the cobalt source in the Co-Si composite material;

[0057] Calculate the mass a of sulfur source required to completely react with the mass n of cobalt source;

[0058] Take a sulfur source with a mass less than a and add it to a mixed solution of 40 mL of deionized water and 40 mL of anhydrous ethanol until the sulfur source is completely dissolved to obtain a colorless transparent solution;

[0059] The dried Co-Si composite material was transferred together with the colorless transparent solution into a 200 mL high-pressure reactor, subjected to solvothermal reaction at 160°C for 8 h, cooled to room temperature, the sample was taken out, and repeatedly washed with deionized water, then placed in a forced air drying oven at 60°C for 6 h to obtain a Co / CoS2 / surface porous Si composite material.

[0060] The dilute strong acid may be dilute hydrochloric acid, and the sulfur source may be sulfur-containing organic matter, such as mercaptans, thiophenols, sulfides, disulfides, thioureas, and the like.

[0061] It should be noted that the values ​​of m and n can be adjusted year-on-year according to actual test conditions, and the value of a can be adjusted according to the type of sulfur source, which is not limited in this embodiment.

[0062] Preferably, in the Co / CoS2 / surface porous Si composite material, the content of Co is 3%-5% of the content of CoS2. Since a small amount of Co is not sulfided, two effective components, Co and CoS2, exist in the composite material at the same time. Co and CoS2 have different catalytic activities and selectivities, and can produce a synergistic effect when used in combination to improve the catalytic efficiency. Co, as a metallic material, easily reacts with other substances during the catalytic process and loses its activity, while CoS2, as an inorganic compound, has high stability. Therefore, the present invention selects a large amount of CoS2 combined with a small amount of Co in the form of ensuring the diversification of catalytic activity, which can keep the composite material stable and thus maintain the catalytic activity.

[0063] Example 2

[0064] This embodiment provides a Co / CoS2 / surface porous Si composite photoelectrocatalytic material, which is prepared by the preparation method of Example 1.

[0065] Figure 1 The XRD pattern of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample in this embodiment is shown in FIG. Figure 1 It can be seen that the diffraction peaks at 2θ of 27.9°, 32.3°, 36.2°, 39.8°, 46.3°, 49.3°, 54.9°, 60.2° and 62.7° correspond to the (111), (200), (210), (211), (220), (221), (311), (222), (230), and (321) crystal planes of CoS2 (JCPDS No. 41-1471). The diffraction peak at 2θ of 69.3° is consistent with the planar Si material and the surface porous Si material, and corresponds to the (400) crystal direction of single crystal silicon (JCPDS No. 80-0018). Moreover, the diffraction peak intensities of silicon in the Co / CoS2 / surface porous Si composite photoelectrocatalytic material, planar Si material, and surface porous Si material are similar, proving that the loading of Co / CoS2 on the surface porous Si substrate has no effect on the strong diffraction peak of silicon. Because the diffraction peak of silicon is too strong, the peak of the loaded CoS2 is masked, but after local magnification, the diffraction peak corresponding to the crystal plane of CoS2 (JCPDS No.41-1471) can still be seen, verifying that the CoS2 nanoparticles have been generated in situ on the surface porous Si substrate.

[0066] Figure 1 This indicates the correct preparation of Co / CoS2 / surface porous Si composite photoelectrocatalytic materials. Due to the low content of Co in the system, no diffraction peak of Co was found, indicating that most of Co has been sulfided into CoS2.

[0067] Figure 2The XPS spectrum of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample in this embodiment is shown in FIG. Figure 2 It can be seen that Co, S and Si elements exist in the sample, which can also be used to prove the successful preparation of Co / CoS2 / surface porous Si composite materials.

[0068] Figure 3 The SEM image of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material sample at 1 μm is shown. Figure 3 It can be seen that octahedral nanoparticles are evenly accumulated around the surface porous Si substrate with good dispersion. From the magnified magnification diagram, it is found that the nanoparticles are deposited more evenly, and the octahedral nanoparticles also provide a path for the refraction of light. The combination of the pore structure and the octahedral structure greatly reduces the surface reflectivity of the Si wafer, which is beneficial to provide more reaction active sites and improve the photoelectrochemical performance.

[0069] The Co / CoS2 / surface porous Si composite photoelectrocatalytic material provided in this embodiment is compared with the planar Si material, the surface porous Si material and the Co / CoS2 / planar Si composite material, and the UV-visible diffuse reflectance spectra of each material are obtained by testing. Figure 4 As shown, from Figure 4 It can be seen that the reflectivity of the planar Si material is greater than that of the surface porous Si material. The reason is that the incident light is reflected multiple times in the pores formed by etching the surface porous Si material, which reduces the overall light reflection of the incident light and more photons are absorbed. The reflectivity of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material is lower than that of the surface porous Si material, mainly because the shape of the loaded Co / CoS2 nanoparticles is an octahedral structure, which can increase the refraction path of the incident light and enhance light absorption, so it has a lower reflectivity. The reflectivity of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material is lower than that of the Co / CoS2 / planar Si material, mainly due to the combination of the surface porous structure and the surface loaded octahedral structure, which greatly enhances light absorption and reduces reflectivity.

[0070] Example 3

[0071] This embodiment provides an application of a Co / CoS2 / surface porous Si composite photoelectrocatalytic material for preparing a photoelectrocatalytic electrode.

[0072] The preparation process of the photoelectrocatalytic electrode includes the following steps:

[0073] The samples were prepared using Co / CoS2 / surface porous Si composite photoelectrocatalytic materials;

[0074] A layer of metallic indium is covered on the back of the sample, and then the copper core wire is fixed on the indium layer with tin wire, and the back and sides of the sample are wrapped with Kraft sealant to ensure that only the front side is in contact with the electrolyte to complete the preparation.

[0075] The improvement of the photoelectric performance of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material mainly depends on the Co / CoS2 powder attached to the surface, and the strength of the Co / CoS2 powder adhesion is closely related to the pores on the surface of the surface porous Si substrate. Therefore, it is necessary to verify the influence of the pores on the surface of the surface porous Si substrate on the photoelectric performance of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material. The formation of the pores is controlled by the etching time. Figure 5 The photo-hydrogen conversion efficiency diagram of Co / CoS2 / surface porous Si composite photoelectrocatalytic material and Co / CoS2 / planar Si material at different etching times is shown. Figure 5 It can be seen that under different etching times, the photo-hydrogen conversion efficiency of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material is always higher than that of the Co / CoS2 / planar Si material, indicating that compared with the planar Si material, the surface porous Si material after etching has better photoelectrochemical water splitting performance. The photo-hydrogen conversion efficiency of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material obtained with an etching time of 45 min is as high as 0.502%, which is better than the etching time of 40 min and 50 min. The reason is that if the etching time is too short, the surface structure of the pores is incomplete, and the reflectivity of the Si substrate is still at a high level, resulting in low light absorption performance; if the etching time is too long, the pores on the surface of the Si substrate are damaged, resulting in fewer light refraction paths, and more incident light is reflected into the air, which has a greater impact on the photoelectrochemical performance of the composite material. Therefore, it is necessary to reasonably select the etching time according to the test results, for example, 45 min.

[0076] Then the effect of Co / CoS2 loading amount on the photoelectric properties of Co / CoS2 / porous Si composite materials was verified. Figure 6 The photo-to-hydrogen conversion efficiency of the samples is shown when the Co / CoS2 loading is 2.1, 3.0 and 3.7 mg, respectively. The CoS2 loading is confirmed by the amount of chemically plated cobalt. Figure 6It can be seen that the maximum photohydrogen conversion efficiency when the loading amount is 2.1mg and 3.7mg is 0.357% and 0.3% respectively, while the maximum photohydrogen conversion efficiency of the photoelectrode when the loading amount is 3.0mg is 0.502%, indicating that the photohydrogen conversion efficiency of the loading amount of 3.0mg is better. The reason is that when the Co / CoS2 loading amount is too small, the photoelectrochemical performance of the composite material is reduced, and the catalytic reaction sites and charge transfer are also reduced; when the loading amount is excessive, the octahedral nanoparticles are stacked together, which reduces the contact area between the porous silicon semiconductor and the electrolyte solution, and prevents the absorption of light, resulting in the hydrogen (oxygen) reaction of the photogenerated holes not being easy to proceed on the surface, which increases the starting potential and reduces the photoelectric performance. Through experiments, it can be obtained that when the loading amount is 3.0mg, the composite material has the most ideal photochemical performance.

[0077] In order to verify the photoelectric performance of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material in this embodiment, it was compared with the Co / CoS2 / planar Si composite material, Co / CoS2 / GCE composite material, surface porous Si material and planar Si material. Figure 7 The photo-to-hydrogen conversion efficiency diagram of the above materials is shown. Figure 7 It can be seen that the photohydrogen conversion efficiency of the planar Si material is relatively low, indicating that its photoelectrochemical performance is relatively poor, and whether it is formed by loading other materials or etching to form a surface porous Si material, the photohydrogen conversion efficiency is doubled. Compared with other materials, the Co / CoS2 / surface porous Si composite photoelectrocatalytic material provided in this embodiment has a greatly improved photoelectric performance, which is due to the combination of the loaded Co / CoS2 powder and the surface porous Si substrate.

[0078] In order to verify the effect of light on the photoelectric performance of Co / CoS2 / surface porous Si composite photoelectrocatalytic materials, the light-to-hydrogen conversion efficiency curves of the samples under strong and weak light conditions were measured, such as Figure 8 As shown, from Figure 8 It can be seen that the maximum photo-to-hydrogen conversion efficiency of the sample under strong light conditions is 0.502%, while the maximum photo-to-hydrogen conversion efficiency of the sample under weak light conditions is 0.006915%. From the comparison, it can be seen that the Co / CoS2 / surface porous Si composite photoelectrocatalytic material provided in this embodiment has good photoelectric properties, indicating that it can be well applied to the photoelectrocatalytic process.

[0079] Finally, the stability of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material in this embodiment was verified. Fig. 9 The stability curve of Co / CoS2 / porous Si composite photoelectrocatalytic material is shown in Figure 2. Fig. 9It can be seen that the photocurrent of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material decreases in the first few minutes, mainly because the photogenerated holes have not reached the electrode to participate in the oxidation and reduction of water molecules, resulting in a certain decrease in the photocurrent density. After the reaction equilibrium, the photocurrent tends to be flat and there is no obvious change within 4 hours, indicating that the Co / CoS2 / surface porous Si composite photoelectrocatalytic material has high stability.

[0080] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a Co / CoS2 / surface porous Si composite photoelectrocatalytic material, characterized in that: The steps include: Step 1, preparing a surface porous Si substrate by using a metal-assisted catalytic etching method; Step 2, using chemical cobalt plating to uniformly deposit a layer of metal Co on the surface of the porous Si substrate to form a Co-Si composite material; Step 3, adding the Co-Si composite material to the sulfur source solution, controlling the sulfur content in the sulfur source solution, so that a small amount of Co in the Co-Si composite material is not sulfurized, and obtaining a Co / CoS2 / surface porous Si composite photoelectrocatalytic material; Step 1 specifically includes the following steps: Cut the Si wafer into pieces with an area of ​​1-2 cm 2 The small pieces were then ultrasonically rinsed with acetone for 15 min, ethanol for 10 min, and ultrapure water for 5 min. Prepare a mixture of concentrated H2SO4 and 30% H2O2 in a volume ratio of 3:1, put the rinsed Si wafer into the mixture, soak it at room temperature for 25 minutes, and then soak it in 5% hydrofluoric acid solution for 2 minutes; A solution of 4.65 mol / L HF, 0.01 mol / L AgNO3 and 0.05 mol / L H2O2 was placed in a plastic cup, which was placed in a water bath at a constant temperature of 60°C. The Si wafer was then placed in the mixed solution in the plastic cup for etching. The etched Si wafer was immersed in concentrated HNO3 for 1 hour to remove the silver particles on the surface and in the pores. After taking it out, the Si wafer was placed in a drying oven and dried at 70°C for 2 hours to obtain a surface porous Si substrate and weigh it accurately. The etching time is 40-50min; The plating solution used for chemical cobalt plating is weakly alkaline and includes cobalt salt, hypophosphite and complexing agent, wherein the cobalt salt is selected from at least one of cobalt chloride and cobalt sulfate, the concentration of the plating solution is selected to be 0.01-0.04 mol / L, the hypophosphite is used as a reducing agent, the concentration is selected to be 0.1-0.25 mol / L, and the complexing agent is selected from one of sodium citrate and tetrahydroxypropylethylenediamine THPED, and the concentration is selected to be 0.03-0.09 mol / L; the specific process of chemical cobalt plating includes the following steps: The surface porous Si substrate is immersed in a 5-10% HF solution for 2 minutes to remove the surface oxide film, and then rinsed with pure water after being taken out; the rinsed surface porous Si substrate is activated with a PdCl2 solution, and then repeatedly rinsed with pure water after activation; the back of the surface porous Si substrate is adhered with a high temperature resistant and corrosion resistant tape to prevent the deposition of a coating on the back of the surface porous Si substrate, and the surface porous Si substrate is immersed in the plating solution for 5-15 seconds to obtain the required Co plating amount, and then repeatedly rinsed with deionized water after being taken out, and dried to obtain a Co-Si composite material; Step 3 specifically includes the following steps: The Co-Si composite material was activated and pretreated with dilute strong acid and anhydrous ethanol, and the activated Co-Si composite material was vacuum dried at 60°C for 3h; Weigh the mass m of the dried Co-Si composite material, and calculate the mass n of the cobalt source in the Co-Si composite material; Calculate the mass a of sulfur source required to completely react with the mass n of cobalt source; Take a sulfur source with a mass less than a and add it to a mixed solution of 40 mL of deionized water and 40 mL of anhydrous ethanol until the sulfur source is completely dissolved to obtain a colorless and transparent solution; The dried Co-Si composite material and the colorless transparent solution were transferred to a 200 mL high-pressure reactor, and the solvent thermal reaction was carried out at 160-170°C for 6-8 hours. The sample was cooled to room temperature, and was taken out and repeatedly washed with deionized water, and then placed in a forced air drying oven at 60°C for 6 hours to obtain a Co / CoS2 / surface porous Si composite material; The dilute strong acid is dilute hydrochloric acid, and the sulfur source is sulfur-containing organic matter.

2. The method for preparing the Co / CoS2 / surface porous Si composite photoelectrocatalytic material according to claim 1, characterized in that: In the Co / CoS2 / surface porous Si composite material, the content of Co is 3%-5% of the content of CoS2.

3. A Co / CoS2 / surface porous Si composite photoelectrocatalytic material, characterized in that: The preparation method is described in any one of claims 1 to 2.

4. An application of the Co / CoS2 / surface porous Si composite photoelectrocatalytic material as claimed in claim 3, characterized in that: Used to prepare photoelectrocatalytic electrodes.

Citation Information

Patent Citations

  • Foam cobalt in-situ vulcanization nanoflower spherical Co4S3@Co hydrogen evolution material and method for preparing same

    CN108889314A

  • Preparation method of cobalt disulfide microspheres with water photolysis oxygen production catalysis assisting function

    CN110605132A